2016
DOI: 10.1007/s11207-016-0901-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparing SSN Index to X-Ray Flare and Coronal Mass Ejection Rates from Solar Cycles 22 – 24

Abstract: The newly revised sunspot number series allows for placing historical geoeffective storms in the context of several hundred years of solar activity. Using statistical analyses of the Geostationary Operational Environmental Satellites (GOES) X-ray observations from the past ≈ 30 years and the Solar and Heliospheric Observatory (SOHO) Large Angle and Spectrometric Coronagraph (LASCO) Coronal Mass Ejection (CME) catalog (1996 -present), we present sunspot-number-dependent flare and CME rates. In particular, we pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…where B denotes the azimuthally averaged radial magnetic field. This formula assumes the use of the Schmidt quasi-normalization in the definition of the spherical harmonics, widely used in solar physics and geomagnetism (see, e.g., Winch et al 2005). For direct comparison of the amplitudes of harmonics of different degree, a full normalization is sometimes preferred (e.g., in DeRosa et al 2012): this results in a normalized dipole coefficientD ¼ ð4p=3Þ 1=2 D. While (12) or even (13) are often loosely referred to as the ''solar dipole moment'', it should also be kept in mind that the magnetic [dipole] moment, as normally defined in physics, is related to D as ð2pR 3 =l 0 ÞD where R is the solar radius and l 0 is the vacuum permeability.…”
Section: Polar Magnetic Field Datamentioning
confidence: 99%
“…where B denotes the azimuthally averaged radial magnetic field. This formula assumes the use of the Schmidt quasi-normalization in the definition of the spherical harmonics, widely used in solar physics and geomagnetism (see, e.g., Winch et al 2005). For direct comparison of the amplitudes of harmonics of different degree, a full normalization is sometimes preferred (e.g., in DeRosa et al 2012): this results in a normalized dipole coefficientD ¼ ð4p=3Þ 1=2 D. While (12) or even (13) are often loosely referred to as the ''solar dipole moment'', it should also be kept in mind that the magnetic [dipole] moment, as normally defined in physics, is related to D as ð2pR 3 =l 0 ÞD where R is the solar radius and l 0 is the vacuum permeability.…”
Section: Polar Magnetic Field Datamentioning
confidence: 99%
“…According to previous research, the number of the CMEs during SC24 is larger than SC23 (Gopalswamy et al 2015a;Winter et al 2016;Compagnino et al 2017; Bilenko 2020), the CMEs during SC24 have lower velocities (Lamy Table 1. The values of the correlation coefficients between CMEs, F10.7, and CBI, during the whole time, SC23, and SC24, respectively.…”
Section: Correlation Analysis Between Cme Occurrence Rate F107 and Cbimentioning
confidence: 77%
“…Lamy et al (2019) analyzed the difference of the CME occurrence rate between the northern and southern hemisphere and confirmed that there exists asymmetry between the two hemispheres. Gopalswamy et al (2015a); Winter et al (2016); Compagnino et al (2017); Bilenko (2020) found that the number of CMEs during Solar Cycle 24 (SC24) is larger than SC23. Bilenko (2020) noted that the high-latitude CMEs contributes more to the increase of the number of CMEs during SC24.…”
Section: Introductionmentioning
confidence: 99%
“…X-class flares are rare, varying from 0 to 20 per year, and those that cause measurable density perturbations, (X-class > X9), even more so. With an occurrence rate of~2 × 10 À3 per day (Winter et al, 2016), we expect only a handful (~8) of X9+ events per solar cycle. This may be a reason for the relative scarcity of studies on the thermospheric response to flares.…”
Section: 1002/2017sw001725mentioning
confidence: 97%